Aineistonhallintaan suunnitelmallisuutta - Tuuli-projekti - Heidi Enwald; Saila Huuskonen; Mari Elisa Kuusniemi; Maria Söderholm (Informaatiotutkimus, 2016)
The importance of research data management planning is emphasized nowadays. The Open Science and Research Initiative (ATT), funders’ and publishers’ requirements put pressures to think how data is collected, organized, archived and shared. Currently, researchers are not always familiar with creating data management plans. The goal of on-going Tuuli-project is to develop a web-based data management planning tool for Finnish research organizations. The tool with templates and guides has potential to support researchers in writing plans for data management.